TRANSNATIONAL CORPORATIONS AS KEY DRIVERS OF ECONOMIC STABILITY AND GLOBAL GROWTH (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This study examines the role of transnational corporations (TNCs) as a key driver of global economic stability and growth. In the context of an increasingly integrated global economy, TNCs play a crucial role not only in the production of goods and services but also in shaping international trade flows, facilitating foreign direct investment (FDI), and promoting technology transfer. The research is based on a comprehensive methodological approach, combining theoretical analysis, empirical data, and statistical methods. Data from United Nations Conference on Trade and Development, World Bank, and International Monetary Fund were used to evaluate the impact of TNCs between 2000 and 2025. The findings indicate that TNCs account for a significant share of global trade through global value chains and contribute substantially to employment, innovation, and economic development, especially in developing countries. At the same time, the study highlights potential challenges, including increased market concentration, inequality, and pressure on local industries.
Keywords: Transnational corporations, global trade flows, foreign direct investment, global value chains, economic stability.